Liquidity management model in non-profit organizations in relation to risk: the case of Polish non-profit organizations - Michalski, Grzegorz; Mercik, Aleksander (Zarządzanie płynnością w polskich organizacjach non-profit, 2012)
The kind of realized mission influences the sensitivity to risk. Among other factors, that risk results from the decision about liquid assets investment level and liquid assets financing. The higher the exposure to risk, the higher the level of liquid assets should be. If the exposure to that risk is smaller, the more aggressive could be the net liquid assets strategy. The organization choosing between various solutions in liquid assets needs to decide what level of risk is acceptable for its owners (or donors) and/or capital suppliers. The paper shows how, in the authors’ opinion, decisions about liquid assets management strategy influence the risk of the organizations and its economical results during the realization of its main mission. Comparing the theoretical model with empirical data for over 3300 Polish non-profit organization results illustrate the way the liquidity management model works for non-profit organizations
Ekonometria = Econometrics, 2012, Nr 1 (35), s. 60-75
Keywords: intrinsic liquidity value; non-profit financial management; financial liquidity; wartość płynności; zarządzanie finansami NPO; płynność finansowa